Empreendedorismo e inovação em vinícolas associadas à Aprovale, Asprovinho e Aprobelo - Pereira, Adrieli Alves (My University, 2014)
The global marketplace is requiring from the enterprises a more strategic approach. Firms are induced to establish defined strategies to reach competitive advantage. Thus, they seek to differentiate themselves through innovative and entrepreneurial activities. The study of entrepreneurship, as a decision-making process, involves the steps and the activities involved in the opportunity perception and the creation of new businesses. Demonstrating an entrepreneurial potential, the rural producers from Serra Gaúcha, were seeking to exploit new entrepreneurial actions, combined with innovative practices. The wine sector of this region has been restructured through strategies in order to gain competitive advantage and a market consolidation, both at the national and the international levels. Nevertheless, this region is still facing difficulties with its performance and competitiveness. This research aims to analyze the strategies used by the wineries associated with APROVALE, ASPROVINHO and APROBELO, from the perspectives of entrepreneurship and innovation. This exploratory study is carried out by means of a multiple case study. In this context, the research is organized into five distinct parts. The first one introduces the research and presents its objectives, the second part develops a literature review, the third part contains the method and its multiple case study, the fourth part brings the analysis and results, and the final part prescribes the considerations, the research limitation and some proposals for further studies. The results show cases peculiarities, their differences and some aspects of convergence in terms of strategy definition.
O mercado globalizado e competitivo está exigindo das empresas uma postura cada vez mais estratégica. As empresas são induzidas a estabelecerem estratégias definidas para obter uma vantagem competitiva. Assim, buscam diferenciar-se com ações empreendedoras e inovadoras. O estudo do empreendedorismo como processo de decisão envolve as etapas e atividades inerentes à percepção e criação de novos negócios. Demonstrando o potencial empreendedor, os produtores rurais da Serra Gaúcha, buscam novas formas de explorar práticas empreendedoras, aliadas com práticas inovadoras. O setor vitivinícola vem se reestruturando através de estratégias, a fim de conquistar vantagens competitivas e consolidação no mercado, tanto nacional, como global. Todavia, essa região tem enfrentado dificuldades em sua performance, quanto à competitividade. O presente trabalho objetiva analisar as estratégias utilizadas por vinícolas associadas à APROVALE, ASPROVINHO e APROBELO sob a ótica do empreendedorismo e da inovação. Trata-se de estudo exploratório realizado por meio de pesquisa de casos múltiplos. Diante do exposto, o trabalho foi organizado em cinco partes distintas. A primeira parte apresenta a introdução e os objetivos; a segunda parte desenvolve a revisão da literatura; a terceira parte contém os procedimentos metodológicos e estudo casos múltiplos; a quarta parte traz as análises e os resultados, a quinta parte, as considerações finais, os limites da pesquisa e as propostas para estudos posteriores. Os resultados apontam as peculiaridades intracaso e o cruzamento de informações intercaso, a fim de destacar pontos similares e divergentes entre as associações.
Keywords: Empreendedorismo; Vale dos Vinhedos, Região (RS); Inovações tecnológicas; Uvas -- Cultivo; Vinho; Vale dos Vinhedos; Associações Vitivinícolas; Inovação; Innovation; Wineries associations